2020
DOI: 10.1210/clinem/dgaa920
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in Diabetic Ketoacidosis Among Patients With Type 1 Diabetes and COVID-19: Data From 52 US Clinical Centers

Abstract: Objective We examined whether diabetic ketoacidosis (DKA), a serious complication of type 1 diabetes (T1D) was more prevalent among Non-Hispanic (NH) Black and Hispanic patients with T1D and laboratory-confirmed coronavirus disease 2019 (COVID-19) compared with NH Whites. Method This is a cross-sectional study of patients with T1D and laboratory-confirmed COVID-19 from 52 clinical sites in the United States, data were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 29 publications
4
46
0
Order By: Relevance
“…People with coronavirus disease 2019 (COVID-19) and preexisting type 1 diabetes (T1D) are at high risk of diabetesrelated outcomes such as diabetic ketoacidosis (DKA) and hospitalization (1). For people with elevated glucose levels, infections could further exacerbate the risk of acute complications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…People with coronavirus disease 2019 (COVID-19) and preexisting type 1 diabetes (T1D) are at high risk of diabetesrelated outcomes such as diabetic ketoacidosis (DKA) and hospitalization (1). For people with elevated glucose levels, infections could further exacerbate the risk of acute complications.…”
mentioning
confidence: 99%
“…We analyzed data from the T1DX COVID-19 Surveillance Registry, a U.S.based multicenter study for people with T1D, to examine the frequency of adverse outcomes across categories of technology use. The registry details have previously been described; briefly, all participating sites completed a chart review and via an online questionnaire submitted information on all patients with T1D at their sites who tested positive for COVID-19 (1,2). This analysis included 447 people with T1D and laboratory-confirmed COVID-19 infection during March 2020-December 2020.…”
mentioning
confidence: 99%
“…COVID-19 outcome severity in T1DM was related to poor glycemic control within the past year (HbA1c ~8%), the presence of chronic complications (hypertension, retinopathy, chronic kidney disease, neuropathy), older age, black ethnicity and low socioeconomic status [ 29 ]. (e) In a recent study, Ebekozien et al [ 30 ] investigated the prevalence of ketoacidosis among 180 non-Hispanic white, non-Hispanic black and Hispanic subjects with T1DM during COVID-19 infection in 52 clinical sites across the USA. The results showed that non-Hispanic blacks were more prone to develop ketoacidosis, suggesting the role of race and ethnicity.…”
Section: T1dm and Covid-19 Disease: Epidemiological Datamentioning
confidence: 99%
“…In contrast to non-Hispanic blacks, most of the non-Hispanic white patients were using insulin pumps and continuous glucose monitoring systems (CGMS) in their treatment. (f) In contrast to these reports, Vangoitsenhoven et al [ 30 ] studied the hospitalization needs of 2336 subjects with T1DM from two diabetes specialist centers in the community during the first 3 months of the pandemic in Belgium. Of this cohort, only 0.21% were admitted to the hospital for treatment, suggesting that their risk for severe outcomes was not increased.…”
Section: T1dm and Covid-19 Disease: Epidemiological Datamentioning
confidence: 99%
“…In a cross-sectional study of subjects with type 1 diabetes and laboratory-confirmed COVID-19 from 52 clinical sites in the United States, Ebekozien et al [ 8 ] showed that the risk of diabetic ketoacidosis in black non-Hispanic patients is 3.7-fold higher than in white non-Hispanic patients.…”
mentioning
confidence: 99%